2015
DOI: 10.7717/peerj.1066
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of genomes, transcriptomes and metabolites of neem tree

Abstract: Neem (Azadirachta indica A. Juss) is one of the most versatile tropical evergreen tree species known in India since the Vedic period (1500 BC–600 BC). Neem tree is a rich source of limonoids, having a wide spectrum of activity against insect pests and microbial pathogens. Complex tetranortriterpenoids such as azadirachtin, salanin and nimbin are the major active principles isolated from neem seed. Absolutely nothing is known about the biochemical pathways of these metabolites in neem tree. To identify genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 49 publications
0
28
1
Order By: Relevance
“…Alignment to the Azadirachta indica A. Juss. chloroplast genome [35] revealed that the largest contig included two inverted repeat regions separated by the large single-copy region. The two remaining 19 Kbp contigs represented both orientations of the small single-copy region; we retained the small single-copy contig that matched the orientation of the A. indica chloroplast genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alignment to the Azadirachta indica A. Juss. chloroplast genome [35] revealed that the largest contig included two inverted repeat regions separated by the large single-copy region. The two remaining 19 Kbp contigs represented both orientations of the small single-copy region; we retained the small single-copy contig that matched the orientation of the A. indica chloroplast genome.…”
Section: Resultsmentioning
confidence: 99%
“…5; see Additional file 1: Figure S3). This phylogeny included the CEOD-NYBG reference, chloroplast genomes we prepared by reference-guided assembly, and two publicly available chloroplast genomes from the Meliaceae: A. indica NC_023792.1 and C. odorata NC_037251.1 [35, 40]. Our alignment for all taxa contained 11,950 SNPs, 1695 of which were segregating within Cedrela taxa (~ 7.6 SNPs/Kbp).…”
Section: Resultsmentioning
confidence: 99%
“…Within breeding programs, various types of molecular markers, such as random amplified polymorphic DNA (RAPD), ribosomal DNA (rDNA), inter-simple sequence repeat (ISSR), sequence characterised amplified region (SCAR), and simple sequence repeat (SSR), have been utilized [ 2 , 3 , 4 , 5 , 6 , 7 ]. Notably, SSRs and single nucleotide polymorphism (SNP) markers are propounded in genetic and plant breeding applications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Azadirachtin A (AZA) is an effective botanical insecticide that is primarily isolated from the seed kernel of the neem tree Azadirachta indica A. Juss (Meliaceae) 18 19 20 and has been widely used as an alternative to synthetic pesticides for controlling various types of agricultural pests because of its non-persistence in the environment and low toxicity against non-target beneficial organisms 21 22 23 . AZA has potent antifeedant and growth inhibitory activities against insects.…”
mentioning
confidence: 99%